1997
DOI: 10.1007/bf02436041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and content of antinutritional factors in Polish cultivars of peas

Abstract: The seeds of 15 Polish pea varieties contained from 221 to 281 g/kg crude protein with a mean of 240.2 +/- 3.5 g/kg dry matter (DM). The weight of 1000 pea seeds, depending on cultivar, ranged from 209.4 to 280.4 g. No interactive effect between the seed mass and the crude protein content was detected. The highest significant negative correlation between weight of seeds and dietary fiber content was r = -0.815XX. The content of dietary fiber ranged from 161.5 to 209.9 g/kg with a mean of 187.9 +/- 3.8 g/kg. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 10 publications
5
20
3
Order By: Relevance
“…Similar results were obtained by Zduńczyk et al (1997) and Smulikowska et al (2001). On the other hand, Gdala et al (1992) found significantly higher TIA, which ranged from 2.68 in white-flowered peas to 4.7 g · kg -1 DM.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results were obtained by Zduńczyk et al (1997) and Smulikowska et al (2001). On the other hand, Gdala et al (1992) found significantly higher TIA, which ranged from 2.68 in white-flowered peas to 4.7 g · kg -1 DM.…”
Section: Discussionsupporting
confidence: 84%
“…Presently, the investigated pea cultivars are characterized by a similar crude protein level in comparison with the cultivars studied by Zduńczyk et al (1997) and Święch et al (2004). No difference was found in the crude protein content of coloured-or white-flower peas, similarly as determined by Gdala et al (1992) and Smulikowska et al (2001).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…At present pea is incorporated into feed mixtures in increased amounts; it is a result of marked expansion of this commodity in the world. This worldwide trend is given by the progress in pea breeding for its higher yield and change in the seed composition (Castell et al, 1996;Zdunczyk et al, 1997;Stanek et al, 2004), mainly for a decrease in antinutritive substances. There exists a considerable variability in chemical composition between and within varieties of pea (Chrenková et al, 1995(Chrenková et al, , 1996(Chrenková et al, , 1998.…”
mentioning
confidence: 99%